2016
DOI: 10.17159/2413-3051/2016/v27i2a1341
|View full text |Cite
|
Sign up to set email alerts
|

Overview of predictive CSP spread prospects and its opportunities

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The sun can be used for heating potential as in Concentrated Solar Energy (CSP) systems, or photon energy in light beams can be used with photovoltaic (PV) systems (Busse and Dinter, 2016). Each system has its own advantages and can be compared with each other using Leveled Cost of Energy (LCOE) (Esram and Chapman, 2007).…”
Section: Conventional and Solar Energymentioning
confidence: 99%
“…The sun can be used for heating potential as in Concentrated Solar Energy (CSP) systems, or photon energy in light beams can be used with photovoltaic (PV) systems (Busse and Dinter, 2016). Each system has its own advantages and can be compared with each other using Leveled Cost of Energy (LCOE) (Esram and Chapman, 2007).…”
Section: Conventional and Solar Energymentioning
confidence: 99%
“…Like most renewable energy systems, there is a need to store the generated energy to be used when the energy source, which is the heat from the sunlight in this case, is not available. For CSP systems, the heat energy can be stored in liquid salt (Busse and Dinter, 2016). Based on the research conducted by Grobbelaar et al (2014), it was found that it will eventually be the case such that CSP technology will be able to overtake traditional power generation systems.…”
Section: Concentrated Solar Power (Csp)mentioning
confidence: 99%
“…Thus, there is an opportunity to consider the effect of adding solar power generation to increase the target set out by the government in the "Electricity for all" programme. The sun can be used for its heating potential as is the case for Concentrated Solar Power (CSP) systems or the photon energy within the light beams can be harnessed with photovoltaic (PV) systems (Busse and Dinter, 2016). Each system has its merits and can be compared against each other using the Levelized Cost of Energy (LCOE) (Esram and Chapman, 2007).…”
Section: Introductionmentioning
confidence: 99%